Analisis prediksi kebangkrutan model zmijewski x-score pada perusahaan subsektor minyak dan gas periode 2019-2021 - Saputro, Dimas Ageng; Hendayana, Yana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to predict financial distress using the Zmijewski X-Score model for oil and gas sub-sector agency listed on the Stock Exchange from 2019-2021. This research uses a qualitative approach method . In this study, the population used were all oil and gas agency listed on the Stock Exchange for the 2019-2021 period, so the population in this study amounted to 14 agency. The sample was selected based on purposive sampling criteria that have been determined, so that the sample in this study amounted to 10 agency. The results of the analysis using the zmijewski model are that in 2019 before the COVID-19 pandemic, there were 4 oil and gas agency in financial distress and 6 oil and gas agency in healthy condition (non-financial distress). In 2020, when the COVID-19 pandemic occurred, there was only 1 company in financial distress and 9 agency still in healthy condition (non-financial distress). In 2021, after the issue of the conflict between Russia and Ukraine, 1 oil and gas company is in financial distress and 9 agency are in a healthy condition (non-financial distress).